SMEs involvement in the Halal industry as part of Fardhu Kifayah’s responsibility - Haslinda Hasan; Geoffrey Harvey Tanakinjal (Asian Scholars Network, 2020)
This concept paper will discuss how the involvement of SMEs in the Halal industry can be considered as fulfilling the Fardhu Kifayah's responsibilities. The concept of Halal and how it relates to Fardhu Kifayah will be discussed based on previous studies and further discussion on how SME involvement in the production and distribution of Halal products contributes to the responsibility of Fardhu Kifayah to the Muslim community. The discussion in this paper is expected to benefit SMEs, all the bodies involved in the development of the Halal industry as well as academics who are interested in studying the concept of Halal and Fardhu Kifayah.